Seasonal variation in hyaluronidase activity in seminal plasma of Murrah buffalo bulls in relation to seminal attributes and effect of thermal protection - MANDAL, D K; NAGPAUL, P K; MOHANTY, A K (The Indian Journal of Animal Sciences, 2014)
Study was conducted to find out the eifect of thermal stress ameluioration and seasonal variation on the hyaluronidase activity (HYA) in seminal plasma of Murrah buffalo bulls. Adult Murrah bulls (12) were divided in 2 equal groups and kept under different thermo-comfortable conditions. Body surface cooling in the experimental group was done by fanning (10 AM to 6 PM) and water sprinkiling 2-4 times during summer (April-June) and 2-times during rainy season (July- October) for 10 min each time. Overall mean (Â± sd) HYA in Murrah buffalo bulls seminal plasma was 5.04Â± 1.94 unit. Between experimental and control groups no significant variation in HYA was observed during summer (6,46Â±1.4vs 7.75Â±0.76) and rainy seasons (4.00Â±1.14 vs 5,46Â±0.56). Thermal stress amelioration had no significant effect on HYA of Murrah buffalo bulls semen, On overall basis hyaluronidase activity in seminal plasma was 7.10Â± 1.28, 4.73Â±1.14 and 3.29Â±0.98 during summer; rainy and winter seasons respectively and the differences were significant (P<0.01). In control group significant seasonal variation in HYA was observed during summer (7.75Â±0.76), rainy (5A6Â±0.56) and winter (3.5.Â±1.04), whereas in the experimental group the difference was significant between summer (6.46Â±1.42) and winter (3.08Â±0.97) only. HYA showed significant negative correlation with mass activity’(-0.83), intitial motility (-0.92), live sperm per cent (-0.97), functional integrity of the spermatozoa (-0.88) and positively (<0.05) associated witH damaged acrosome (0.98), abnormal head (0.86) and total abnormal sperm per cent (0.99): It was concluded that seasons significantly influenced the hyaluronidase activity of seminal plasma of Murrah buffalo bulls, however, thermal stress amelioration by body surface cooling did not show any significant effect on the Same. Higher level of hyaluronidase activity in seminal plasma of neat semen of Murrah buffalo bulls, the poorer the quality of semen.